Locality Requirements in Reduplication: SyllableProximity-BR - Peter Ara Guekguezian (Amherst demo, 2014)
Some languages show patterns of order-disrupting reduplication, in which the input order of elements is not faithfully preserved in the reduplicated form. Based on data from Saisiyat, an endangered Austronesian language of Taiwan, I propose that these patterns of order-disrupting reduplication are driven by syllable-based locality. In Saisiyat Progressive Reduplication, the second occurrence of the elements in Base-Reduplicant correspondence interrupts the expected linear sequence; for example, the unreduplicated form [koma:at] 'write' has the reduplicated form [kokma:at] 'be writing', in which the second [k] is order-disrupting. To account for such patterns, I propose a constraint SyllableProximity-BR, which demands that elements in Base-Reduplicant correspondence be dominated by the same syllable node. Order disruption results when SyllableProximity-BR dominates a constraint requiring order preservation. This account captures both the position and the minimal size of the Reduplicant in order-disrupting reduplication, and makes the strong empirical prediction that all order-disrupting reduplication is local. An alternative account of these phenomena that enforces position and size requirements by separate constraints predicts unattested patterns of order-disrupting reduplication with a variable source of copy and an arbitrarily long distance between correspondents.
Keywords: Austronesian; reduplication; locality